Message in a bottle - Sparks, Nicholas (New York : Warner Books, 1999)
A 36-year-old single mother finds a bottle containing a love letter written only three weeks earlier by a man declaring his love to his darling Catherine. She decides to try to make contact with the man in hopes of changing both their lives.
Keywords: Ocean bottles -- Massachusetts -- Fiction; Love stories